Neustar. Inc: the challenges of diversification - McDonald, Michael (Henry Stewart Talks, 2015)
Neustar origins, Capital usage decision, Abbreviated balance sheet, Abbreviated income statement, Diversification options, Valuing the options, Diversification outcomes